2013
DOI: 10.1115/1.4024865
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on a Medium Consistency Pump

Abstract: An experimental testing rig is built to study the performance of a centrifugal pump used in medium consistency technology (MC technology). Pump performances are tested in different pulp concentration, degas pressure differential, and tip clearance ratio. The results show that in medium concentration, pump head and efficiency decreases with increase of pulp concentration. There is a critical concentration above which pump performance drops. Gas separation effect is influenced by the pressure differential over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…HF Zhuang, 12 in 2012, investigated the effects of different speeds and vacuum pressure on the consistency pulp performance, and the result showed that increase in the pump speed and the degree of vacuum can improve MC pump performance. In 2014, XD Ma 13,14 analyzed the hydraulic structure of MC pump and built-in pump performance test platform to study the change in different pulp concentrations, the impeller exit width, and degree of vacuum in the operating characteristics of pump. However, there is lack of relevant consistency pulp pump design theory.…”
Section: Introductionmentioning
confidence: 99%
“…HF Zhuang, 12 in 2012, investigated the effects of different speeds and vacuum pressure on the consistency pulp performance, and the result showed that increase in the pump speed and the degree of vacuum can improve MC pump performance. In 2014, XD Ma 13,14 analyzed the hydraulic structure of MC pump and built-in pump performance test platform to study the change in different pulp concentrations, the impeller exit width, and degree of vacuum in the operating characteristics of pump. However, there is lack of relevant consistency pulp pump design theory.…”
Section: Introductionmentioning
confidence: 99%
“…Medium-consistency (MC) technology was first developed in Northern Europe in 1970s. 1,2 Then, it was widely used to pump, stock, beat, bleach, and filter pulp suspensions at medium concentration with its advantages of high energy efficiency and low environmental effects. MC pump is an important piece of equipment in the MC pumping process.…”
Section: Introductionmentioning
confidence: 99%